2020
DOI: 10.3389/fendo.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Health, Insulin, and Breast Cancer: Why Oncologists Should Care About Insulin

Abstract: The potential association between obesity and TNBC has been a subject of intense research study. As outlined below, studies investigating the potential relationship between obesity and TNBC have been inconsistent. This is a summary of some of the key studies that have been recently published.The Carolina Breast Cancer Study is a North Carolina population-based case-controlled study of breast cancer, conducted in three phases (28). The current study phase, Phase 3 (years 2008-2014), includes women resident in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 233 publications
(335 reference statements)
0
42
0
Order By: Relevance
“…Moreover, women with triple-negative tumors seem to have a high prevalence of metabolic syndrome, characterized by increased BMI and circulating levels of insulin and related growth factors, leading to uncontrolled cell proliferation [ 44 ] and worse prognosis. Several other studies were conducted to investigate the potential role of obesity in TNBC development, with controversial results [ 45 ].…”
Section: Host Metabolism and Breast Cancer Prognosismentioning
confidence: 99%
“…Moreover, women with triple-negative tumors seem to have a high prevalence of metabolic syndrome, characterized by increased BMI and circulating levels of insulin and related growth factors, leading to uncontrolled cell proliferation [ 44 ] and worse prognosis. Several other studies were conducted to investigate the potential role of obesity in TNBC development, with controversial results [ 45 ].…”
Section: Host Metabolism and Breast Cancer Prognosismentioning
confidence: 99%
“…However, IR-A is intimately linked to the mitogenic MAPK/mammalian target of rapamycin (mTOR) cascade rather than to the PI3K/Akt metabolic cascade also in response to insulin ( Frasca et al, 1999 ). As a consequence, BC cells do not share the insulin resistance of peripheral tissues of obese patients ( Yee et al, 2020 ). Therefore, IR-A overexpression can be seen as a way BC cells exploit to overcome insulin resistance of obese patients and allow full response to the estrogen/IIGFs cross-talk ( Belfiore et al, 2017 ).…”
Section: Estrogen and Iigfs Signaling In Bcmentioning
confidence: 99%
“…When exposed to hyperinsulinemia, cancer cells gain a selective growth advantage compared to normal tissues [ 46 ]. It has been found that the higher breast cancer incidence and higher all-cause mortality after breast cancer were significantly correlated with higher levels of insulin resistance in postmenopausal women [ 49 , 50 ]. Analyzing protein–protein interaction network in STRING database, SLC2A4 also participates in the translocation of SLC2A4 ( GLUT4 ) to the plasma membrane and protein localization to plasma membrane through enriched proteins such as EXOC5 and C2CD5 , which play an important role in human cancers.…”
Section: Discussionmentioning
confidence: 99%